Oxidized regenerated cellulose cross-linked gelatin microparticles for rapid and biocompatible hemostasis: A versatile cross-linking agent. (15th November 2018) - Aydemir Sezer, Umran; Kocer, Zeynep; Sahin, İsa and Aru, Basak and Yanıkkaya Demirel, Gulderen and Sezer, Serdar
Graphical abstract: Highlights: ORC is first ever used as a cross-linking agent and also examines its potential in medical applications. The ORC-crosslinked gelatin microparticles developed is found both biocompatible and efficiently hemostatic. Better hemostatic performance of Gel-NaORCl material as compared to other NaORC-containing group is established. Gel-NaORC1 also found to yield better scores of platelets activation than Gel and NaORC alone. Abstract: Effective hemostatic materials are of utmost importance for preventing bleeding in emergencies and critical injuries. Combining biodegradability, good hemostatic properties and biocompatibility, gelatin is one of the most reliable materials clinically used for preventing internal bleeding in surgeries and for stopping external hemorrhage. Cross-linking is a useful method for enhancing the absorption capacity of gelatin and for controlling the degradation process. Existing and commonly used aldehyde-containing cross-linking agents lack reliability with respect to the control of hemostatic effect, solubility and toxicity. In this study; gelatin was cross-linked with sodium oxidized regenerated cellulose (NaORC) to produce hemostatic microparticles. The NaORC was used at different ratios; and the studies on hemostatic efficiency and cytotoxicity under in vitro conditions demonstrated rapid arrest of bleeding alongside biocompatibility. These microparticles employing NaORC as a cross-linking agent for the first time demonstrated a unique structure for stopping bleeding with biocompatibility, and opened the way for different forms of cross-linked structures to be used in other biomaterials applications.